A 5-year follow-up of Girdlestone resection arthroplasty in hip infection continued by Total hip replacement: A case report. (April 2022) - Solichin, Iman; Putera, Guntur Utama; Kuncoro, Mohamad Walid
Abstract: Introduction: Resection arthroplasty of the hip was already performed for recent 100 years. This kind of surgery has been used for a wide variety of hip problems such as infection, degenerative osteoarthritis and prosthetic joint infection. Total hip replacement is remarkable procedure in order to relieve pain and restore hip function. We present this report to describe our experience in treating hip infection by used two stages of surgery. Case presentation: A 61-years old male suffered left hip infection that leads severe destruction on his joint. He felt badly pain on his hip with significant disability associated it such as limping, restriction of movements, and shortening of the limb. The hip movements were painful and caused walking in antalgic gait. Radiologic examination at that time revealed gross destruction of femoral head as well as acetabulum, irregular and hazy joint margins with diminished joint space. Patient was diagnosed with chronic non-specific inflammation of the hip joint. Result: Two stages surgery were performed on this patient. Resection arthroplasty firstly performed in order to eradicate the infection completely and alleviate very bothersome pain for improvement of patient's quality of life. Two years later, after patient was ready for next stage mentally, cemented total hip replacement performed to achieve normal function of the hip. Five-years follow up functional outcome was performed. Patient was very satisfied with the result with Harris hip scores was 95. Conclusion: Resection arthroplasty of the hip followed by a conversion to total hip replacement in hip infection case provide complete infection eradication, good functional outcome and satisfaction for the patient. Although the procedure was time-consuming it can be a choice if the eradication of infection still in a doubt.